Go Referee Appication for Futsal Association at Wonosobo Regency - arifin, zainal; Sulaiman, Sulaiman; Irawan, Fajar Awang (Journal of Physical Education and Sports, 2021)
Android is the most widely used operating system for smartphones. The Go-Referee Application is currently being developed as a learning media solution that incorporates knowledge technology on Referee Databases, Game Rules, and Professional Referee Video Guides. Android application development might be a useful tool for cognitive-based learning. It can assist futsal referees with their psychomotor development. The purpose of this study was to examine and analyze the model and development of an Android-based Go-Referee application for the Wonosobo Regency Futsal Union in Central Java. Research and development method was sued, with Sugiyono's research steps adapted to ten. The research was conducted on teams or members of the Wonosobo Regency Futsal Association in Central Java, including AFK administrators, referees, futsal event organizers, and futsal fans. The results showed that the development of the Android-based Go-Referee Application was successful and feasible for use as a training medium to assist Wonosobo futsal referees in deepening their knowledge of futsal refereeing and in locating referees with District, Province, and National Licenses. If the material expert validation score was 100%, showing very possible, 94%, indicating decent/good. The Go Referee application received a 91.6 % assessment score in the small group trial, putting it in the good/decent category, and a 92.1 % assessment score in the large group trial, putting it in the appropriate/good category. Go Referee application was determined to be a technologically advanced sports development breakthrough that made it easier for referees and the Wonosobo community to obtain a licensed referee database in Wonosobo.